Outcome Analysis Following Microvascular Free Gracilis Muscle Transfer for Multi-Vector Facial Reanimation - Muhammad Izzuddin Hamzan; Mior Faiq Abu Tahrin; Wan Azman Wan Sulaiman (Tropical Health and Medical Research, 2021)
The purpose of this research to address objective excursion and symmetry results from a series of free gracilis muscle transfer (FGMT) cases and examine the predictive intraoperative number of vectors anchored during flap inset on outcomes. A retrospective analysis performs by data retrieved from the HUSM Plastic & Reconstructive Surgery OR Registry from January 2005 to June 2019. All patients who reported facial nerve palsy were recorded and re-evaluated. All characteristics in interest were epidemiologically tabulated and analyzed in detail. Subsequently, outcome assessment was performed to look for facial symmetry and smile excursion compared to the healthy side of the face—this study exempted by the Institutional Review Board of the Hospital of University of Sciences Malaysia. Out of 12 patients diagnosed with facial palsy, four patients underwent static facial reanimation. Eight patients underwent a dynamic facial reanimation, with 4 of them completed two stages of cross-facial nerve grafting (CFNG) and free gracilis muscle transfer (FGMT). One of the FGMTs patients had missed a follow-up. The mean age was 20 (range 11 to 30), one patient was male, and two were female. The mean duration for follow-up was 69 months. The mean duration of operating time was 8.67 hours. All operations without complication, and there was no microvascular re-exploration. Smile excursion and angle excursion at smile improved following FGMT. Association between the number of vectors anchored during flap inset to the outcome were identified. Dynamic facial reanimation using FGMT still the gold standard of treatment, which provides an excellent quantifiable improvement in oral commissure excursion and facial symmetry with smiling. The use of multivector gracilis flap was suggestive to associate with the good outcome on excursion and symmetrical of the smile.